(untitled) (Manila, 1971)
Descriptions of the Philippines by the travelers listed below, giving their nationality, and year the resided in the islands, or the approximate year when they wrote the accounts.
Keywords: Philippines,Philippines; Description and travel,Mô tả và du lịch